Preparation and Application of Epoxy Oil-Based Fire-Retardant Plasticizer for PVC - Feng, Guo-Dong; Hu, Yun; Zhou, Yong-Hong (Asian Journal of Chemistry, 2015)
An epoxy oil-based fire-retardant plasticizer with a triazine ring structure (THEIC-SBOE) has been prepared by transesterification and epoxidation using tris(2-hydroxyethyl)isocyanurate and soybean oil methyl ester as the main raw materials. The structure of THEIC-SBOE has been characterized by FTIR, 1H NMR and 13C NMR spectroscopies and elemental analysis and its thermal stability has been measured by thermogravimetric analysis. Its epoxy value and acid value have been determined as 4.3 % and 0.6 mg KOH g-1, respectively. Examination of the morphology of carbon residue from PVC by scanning electron microscopy showed THEIC-SBOE to serve as an intumescent flame retardant. The results showed that, with the same plasticizer contents incorporated into PVC, THEIC-SBOE imparted similar mechanical properties as epoxidized soybean oil. Furthermore, PVC blends incorporating the synthesized plasticizer THEIC-SBOE displayed better fire-retardant properties than those incorporating dioctyl phthalate. The limiting oxygen index of such a PVC blend reached 28.4 % with 35 % (w/w) THEIC-SBOE incorporation.